Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2016)
The United States and India have pledged to deepen the linkages between their people, their businesses, and their governments for the mutual benefit of both countries and for the promotion of global peace, stability, economic growth and prosperity. Both nations are now inclined to improve relations and cooperation, but the nations need specific actions that will yield progress and build confidence and momentum for further cooperation. The Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety, held in November 2014, encouraged scientists from both countries to examine global issues related to emerging and existing infections and global health safety, to share experience and approaches, and to identify opportunities for cooperation to improve practice and research in these areas. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Science Literacy: Concepts, Contexts, and Consequences - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Science is a way of knowing about the world. At once a process, a product, and an institution, science enables people to both engage in the construction of new knowledge as well as use information to achieve desired ends. Access to science—whether using knowledge or creating it—necessitates some level of familiarity with the enterprise and practice of science: we refer to this as science literacy.
Keywords: Education

Preventing Bullying Through Science, Policy, and Practice - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Bullying has long been tolerated as a rite of passage among children and adolescents. There is an implication that individuals who are bullied must have "asked for" this type of treatment, or deserved it. Sometimes, even the child who is bullied begins to internalize this idea. For many years, there has been a general acceptance and collective shrug when it comes to a child or adolescent with greater social capital or power pushing around a child perceived as subordinate. But bullying is not developmentally appropriate; it should not be considered a normal part of the typical social grouping that occurs throughout a child's life. Although bullying behavior endures through generations, the milieu is changing. Historically, bulling has occurred at school, the physical setting in which most of childhood is centered and the primary source for peer group formation. In recent years, however, the physical setting is not the only place bullying is occurring. Technology allows for an entirely new type of digital electronic aggression, cyberbullying, which takes place through chat rooms, instant messaging, social media, and other forms of digital electronic communication. Composition of peer groups, shifting demographics, changing societal norms, and modern technology are contextual factors that must be considered to understand and effectively react to bullying in the United States. Youth are embedded in multiple contexts and each of these contexts interacts with individual characteristics of youth in ways that either exacerbate or attenuate the association between these individual characteristics and bullying perpetration or victimization. Recognizing that bullying behavior is a major public health problem that demands the concerted and coordinated time and attention of parents, educators and school administrators, health care providers, policy makers, families, and others concerned with the care of children, this report evaluates the state of the science on biological and psychosocial consequences of peer victimization and the risk and protective factors that either increase or decrease peer victimization behavior and consequences.
Keywords: Behavioral and Social Sciences

Extending Science: NASA's Space Science Mission Extensions and the Senior Review Process - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
NASA operates a large number of space science missions, approximately three-quarters of which are currently in their extended operations phase. They represent not only a majority of operational space science missions, but a substantial national investment and vital national assets. They are tremendously scientifically productive, making many of the major discoveries that are reported in the media and that rewrite textbooks. Extending Science – NASA's Space Science Mission Extensions and the Senior Review Process evaluates the scientific benefits of missions extensions, the current process for extending missions, the current biennial requirement for senior reviews of mission extensions, the balance between starting new missions and extending operating missions, and potential innovative cost-reduction proposals for extended missions, and makes recommendations based on this review.
Keywords: Space and Aeronautics

Making the Living World Engineerable: Science, Practice, and Policy: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On November 16, 2016, the Forum on Synthetic Biology of the National Academies of Sciences, Engineering, and Medicine's Committee on Science, Technology, and Law hosted a workshop titled Making the Living World Engineerable: Science, Practice, and Policy. The workshop was organized by an ad hoc planning committee to discuss current trends in synthetic biology, including international scientific and technical developments in synthetic biology; possible risks and benefits related to these developments; and legal, regulatory, and policy concerns. This Proceedings of a Workshop-in Brief highlights the presentation of the event.
Keywords: Policy for Science and Technology; Biology and Life Sciences

Achieving Science with CubeSats: Thinking Inside the Box - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Space-based observations have transformed our understanding of Earth, its environment, the solar system and the universe at large. During past decades, driven by increasingly advanced science questions, space observatories have become more sophisticated and more complex, with costs often growing to billions of dollars. Although these kinds of ever-more-sophisticated missions will continue into the future, small satellites, ranging in mass between 500 kg to 0.1 kg, are gaining momentum as an additional means to address targeted science questions in a rapid, and possibly more affordable, manner. Within the category of small satellites, CubeSats have emerged as a space-platform defined in terms of (10 cm x 10 cm x 10 cm)- sized cubic units of approximately 1.3 kg each called "U's." Historically, CubeSats were developed as training projects to expose students to the challenges of real-world engineering practices and system design. Yet, their use has rapidly spread within academia, industry, and government agencies both nationally and internationally. In particular, CubeSats have caught the attention of parts of the U.S. space science community, which sees this platform, despite its inherent constraints, as a way to affordably access space and perform unique measurements of scientific value. The first science results from such CubeSats have only recently become available; however, questions remain regarding the scientific potential and technological promise of CubeSats in the future. Achieving Science with CubeSats reviews the current state of the scientific potential and technological promise of CubeSats. This report focuses on the platform's promise to obtain high- priority science data, as defined in recent decadal surveys in astronomy and astrophysics, Earth science and applications from space, planetary science, and solar and space physics (heliophysics); the science priorities identified in the 2014 NASA Science Plan; and the potential for CubeSats to advance biology and microgravity research. It provides a list of sample science goals for CubeSats, many of which address targeted science, often in coordination with other spacecraft, or use "sacrificial," or high-risk, orbits that lead to the demise of the satellite after critical data have been collected. Other goals relate to the use of CubeSats as constellations or swarms deploying tens to hundreds of CubeSats that function as one distributed array of measurements.
Keywords: Space and Aeronautics

From Research to Reward: Social Science Studies the Most Hazardous Thing on the Road: You - National Academy of Sciences (The National Academies Press, 2016)
Keywords: Explore Science; Behavioral and Social Sciences

Applying an Implementation Science Approach to Genomic Medicine: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Although it is becoming increasingly more common for clinicians to use genomic data in their practices for disease prevention, diagnosis, and treatment, the process of integrating genomic data into the practice of medicine has been a slow and challenging one. Some of the major barriers impeding the incorporation of new genomic technology into clinical practice are: the difficulty of changing routine medical practices to account for the use of genetic testing, the limited knowledge of patients and providers about genomic medicine, assessing sufficient evidence to support the use of genetic tests, privacy and data security issues, and uncertainty about reimbursement.
Keywords: Health and Medicine

Communicating Chemistry: A Framework for Sharing Science: A Practical Evidence-Based Guide - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
A growing body of evidence indicates that, increasingly, the public is engaging with science in a wide range of informal environments, which can be any setting outside of school such as community-based programs, festivals, libraries, or home. Yet undergraduate and graduate schools often don’t prepare scientists for public communication.
Keywords: Math, Chemistry, and Physics; Education

Gene Drives on the Horizon: Advancing Science, Navigating Uncertainty, and Aligning Research with Public Values - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Research on gene drive systems is rapidly advancing. Many proposed applications of gene drive research aim to solve environmental and public health challenges, including the reduction of poverty and the burden of vector-borne diseases, such as malaria and dengue, which disproportionately impact low and middle income countries. However, due to their intrinsic qualities of rapid spread and irreversibility, gene drive systems raise many questions with respect to their safety relative to public and environmental health. Because gene drive systems are designed to alter the environments we share in ways that will be hard to anticipate and impossible to completely roll back, questions about the ethics surrounding use of this research are complex and will require very careful exploration. Gene Drives on the Horizon outlines the state of knowledge relative to the science, ethics, public engagement, and risk assessment as they pertain to research directions of gene drive systems and governance of the research process. This report offers principles for responsible practices of gene drive research and related applications for use by investigators, their institutions, the research funders, and regulators.
Keywords: Biology and Life Sciences

From Research to Reward: The Hospital Checklist: How Social Science Insights Improve Health Care Outcomes - National Academy of Sciences (The National Academies Press, 2016)
Keywords: Explore Science; Policy for Science and Technology; Behavioral and Social Sciences; Health and Medicine

Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions: Workshop in Brief - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On October 6, 2015, the Roundtable on Obesity Solutions of the National Academies of Sciences, Engineering, and Medicine held a workshop titled "Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions." The workshop examined what is currently known about the prevalence of obesity in young children, its trends over time, and its persistence into later childhood, adolescence, and adulthood; epigenetic factors related to risk of early childhood obesity; and the development of taste and flavor preferences in the first few years of life. The workshop explored recent developments in the science of modifiable protective and risk factors associated with obesity through age 5, including a mother's pre-pregnancy weight and weight gain during pregnancy; smoking during pregnancy; breastfeeding; complementary feeding, responsive parenting; and sleep, activity, and sedentary behavior in young children.
Keywords: Food and Nutrition; Health and Medicine

Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Among the many troubling aspects of the rising prevalence of obesity in the United States and elsewhere in recent years, the growth of early childhood overweight and obesity stands out. To explore what is known about effective and innovative interventions to counter obesity in young children, the National Academies of Sciences, Engineering, and Medicine’s Roundtable on Obesity Solutions held a workshop in October 2015. The workshop brought together many of the leading researchers on obesity in young children to describe the state of the science and potential solutions based on that research. Participants explored sustainable collaborations and new insights into the implementation of interventions and policies, particularly those related to nutrition and physical activity, for the treatment and prevention of obesity in young children. Obesity in the Early Childhood Years summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Supporting Family and Community Investments in Young Children Globally: Summary of a Joint Workshop by the National Academies of Sciences, Engineering, and Medicine and the Ethiopian Academy of Sciences - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
To examine the science, policy, and practice surrounding supporting family and community investments in young children globally and children in acute disruptions, the National Academies of Sciences, Engineering, and Medicine held a workshop in partnership with the Ethiopian Academy of Sciences in Addis Ababa, Ethiopia, from July 27-29, 2015. The workshop examined topics related to supporting family and community investments in young children globally. Examples of types of investments included financial and human capital. Participants also discussed how systems can better support children, families, and communities through acute disruptions such as the Ebola outbreak. Over the course of the 3-day workshop, researchers, policy makers, program practitioners, funders, young influencers, and other experts from 19 countries discussed how best to support family and community investments across areas of health, education, nutrition, social protection, and other service domains. This report summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Advancing the Discipline of Regulatory Science for Medical Product Development: An Update on Progress and a Forward-Looking Agenda: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The field of endeavors known as "regulatory science" has grown out of the need to link and integrate knowledge within and among basic science research, clinical research, clinical medicine, and other specific scientific disciplines whose focus, aggregation, and ultimate implementation could inform biomedical product development and regulatory decision making. Substantial efforts have been devoted to defining regulatory science and communicating its value and role across the scientific and regulatory ecosystems. Investments are also being made in technology infrastructure, regulatory systems, and workforce development to support and advance this burgeoning discipline.
Keywords: Health and Medicine

Future Directions for NSF Advanced Computing Infrastructure to Support U.S. Science and Engineering in 2017-2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Advanced computing capabilities are used to tackle a rapidly growing range of challenging science and engineering problems, many of which are compute- and data-intensive as well. Demand for advanced computing has been growing for all types and capabilities of systems, from large numbers of single commodity nodes to jobs requiring thousands of cores; for systems with fast interconnects; for systems with excellent data handling and management; and for an increasingly diverse set of applications that includes data analytics as well as modeling and simulation. Since the advent of its supercomputing centers, the National Science Foundation (NSF) has provided its researchers with state-of-the-art computing systems. The growth of new models of computing, including cloud computing and publically available by privately held data repositories, opens up new possibilities for NSF.
Keywords: Computers and Information Technology

An Assessment of the National Institute of Standards and Technology Center for Nanoscale Science and Technology: Fiscal Year 2016 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
At the request of the National Institute of Standards and Technology (NIST), the National Academies of Sciences, Engineering, and Medicine has, since 1959, annually assembled panels of experts from academia, industry, medicine, and other scientific and engineering communities to assess the quality and effectiveness of the NIST measurements and standards laboratories, of which there are now seven, as well as the adequacy of the laboratories’ resources. An Assessment of the National Institute of Standards and Technology Center for Nanoscale Science and Technology: Fiscal Year 2016 assesses the scientific and technical work performed by the NIST Center for Nanoscale Science and Technology and the accomplisments, challenges, and opportunities for improvement.
Keywords: Engineering and Technology; Industry and Labor

Art, Design and Science, Engineering and Medicine Frontier Collaborations: Ideation, Translation, Realization: Seed Idea Group Summaries (The National Academies Press, 2016)
Science and art were not always two separate entities. Historically, times of great scientific progress occurred during profound movements in art, the two disciplines working together to enrich and expand humanity's understanding of its place in this cosmos. Only recently has a dividing line been drawn, and this seeming dichotomy misses some of the fundamental similarities between the two endeavors.
Keywords: Policy for Science and Technology

Reaching and Investing in Children at the Margins: Summary of a Joint Workshop by the National Academies of Sciences, Engineering, and Medicine; Open Society Foundations; and the International Step by Step Association (ISSA) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The United Nations Sustainable Development Goals for 2015-2030 strive for a world that is "just, equitable, and inclusive," in which everyone receives care, education, and opportunities to thrive. Yet many children are living on the margins of society, face multiple disadvantages, and are excluded from full participation in all that life has to offer. To examine the science, economics, and politics of investing in the health, education, nutrition, and social protection of children at the margins, the National Academies of Sciences, Engineering, and Medicine held a workshop in Prague, Czech Republic in November 2015. Held in partnership with the Open Society Foundations and the International Step by Step Association, the workshop convened a diverse group of stakeholders from around the world for 2 days of discussion. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences

Investing in Young Children for Peaceful Societies: Proceedings of a Joint Workshop by the National Academies of Sciences, Engineering, and Medicine; UNICEF; and the King Abdullah Bin Abdulaziz International Centre for Interreligious and Intercultural Dialogue (KAICIID) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
With the worst human refugee crisis since World War II as the backdrop, from March 16 through March 18, 2016, the National Academies of Sciences, Engineering, and Medicine, in partnership with UNICEF and the King Abdullah Bin Abdulaziz International Center for Inter-religious and Intercultural Dialogue (KAICIID), held a workshop in Amman, Jordan, to explore topics related to investing in young children for peaceful societies. Over the course of the workshop, researchers, policy makers, program practitioners, funders, youth, and other experts came together to understand the effects of conflict and violence on children, women, and youth across areas of health, education, nutrition, social protection, and other domains. The goal of the workshop was to continue to fill in gaps in knowledge and explore opportunities for discourse through a process of highlighting the science and practice. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences